HDAC inhibitors trigger apoptosis in HPV-positive cells by inducing the E2F-p73 pathway - Finzer, Patrick; Krammer, Peter H.; Rösl, Frank (Oncogene, 2004)
Histone deacetylase (HDAC) inhibitors induce an intrinsic type of apoptosis in human papillomavirus (HPV)-positive cells by disrupting the mitochondrial transmembrane potential (ΔΨm). Loss of ΔΨm was only detected in E7, but not in E6 oncogene-expressing cells. HDAC inhibition led to a time-dependent degradation of the pocket proteins pRb, p107 and p130, releasing ‘free’ E2F-1 following initial G1 arrest. Inhibition of proteasomal proteolysis, but not of caspase activity rescued pRb from degradation and functionally restored its inhibitory effect on the cyclin E gene, known to be suppressed by pRb-E2F-1 in conjunction with HDAC1. Using siRNA targeted against p53, E2F-1 still triggered apoptosis by inducing the E2F-responsive proapoptotic α- and β-isoforms of p73. These data may determine future therapeutic strategies in which HDAC inhibitors can effectively eliminate HPV-positive cells by an apoptotic route that does not rely on the reactivation of the ‘classical’ p53 pathway through a preceding shut-off of viral gene expression.
Gesehen am 06.04.2021